Comparative Study on the Pretreatment of Aspen and Maple With 1-Ethyl-3-methylimidazolium Acetate and Cholinium Lysinate - Choudhary, Hemant; Simmons, Blake A.; Gladden, John M. (Frontiers in Energy Research, 2022)
The efficiency of the enzymatic digestibility of certain lignocellulosic biomass has been observed as a function of their structural and chemical changes which in turn depends on the ionic liquid (IL) employed as the pretreatment solvent. This study demonstrates and compare the feasibility of IL pretreatment process for two woody biomasses namely Maple and Aspen using two mechanistically distinct ILs i.e., 1-ethyl-3-methylimidazolium acetate ([C2mim][OAc]) and cholinium lysinate ([Ch][Lys]) as the solvent. The pretreatment was performed at three different temperatures of 100 °C, 140 °C, and 160 °C at a high solid loading of 25wt% to understand the impact of lignin content and crystallinity index on enzymatic digestibility. Saccharification of the biomass obtained after the IL-pretreatment afforded 30-85% glucan conversions. For Aspen, both [C2mim][OAc] and [Ch][Lys] exhibited highest glucan conversion at 140 °C. For Maple, highest glucan conversion was obtained at 140 °C with [C2mim][OAc], whereas, [Ch][Lys] had optimum glucan conversion at 160 °C. These pretreatments resulted in negligible delignification irrespective of the IL employed. A significant loss of crystallinity was observed for all [C2mim][OAc] pretreated biomasses, whereas the pretreatment with [Ch][Lys] resulted in an increase in the crystallinity index.